2020
DOI: 10.1111/iej.13316
|View full text |Cite
|
Sign up to set email alerts
|

Does tobacco smoking predispose to apical periodontitis and endodontic treatment need? A systematic review and meta‐analysis

Abstract: BackgroundControversial findings exist in the literature regarding the association between tobacco smoking and development of apical periodontitis or need for root canal treatment, with some studies reporting an increase in the prevalence of these outcomes in smokers, whilst others reporting no association.AimTo evaluate if there is scientific evidence to support an association between tobacco smoking and a greater prevalence of apical periodontitis and/or root canal treatments.Data SourcesA systematic search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
1
22
0
2
Order By: Relevance
“…2019, Pinto et al . 2020). Similarly, several other studies have reported that genetic predisposition may also influence the development of CVDs (Bis et al .…”
Section: Discussionmentioning
confidence: 99%
“…2019, Pinto et al . 2020). Similarly, several other studies have reported that genetic predisposition may also influence the development of CVDs (Bis et al .…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence of periapical radiolucencies in smoking patients has been described with moderate evidence in a recent systematic review (Pinto et al . 2020a). Smoking was also significantly associated with a negative tooth survival status when comparing root canal treatment performed in BPs patients and treatment performed in healthy patients (as shown in Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…2017, Pinto et al . 2020). However, to date there are no published studies evaluating the influence of nicotine consumption or simultaneous alcohol and nicotine consumption on apical periodontitis in rats.…”
Section: Introductionmentioning
confidence: 99%